Outcomes of Venovenous Extracorporeal Membrane Oxygenation When Stratified by Age: How Old Is Too Old?. Issue 8 (August 2020) - Deatrick, Kristopher B.; Mazzeffi, Michael A.; Galvagno, Samuel M.; Tesoriero, Ronald B.; Kaczoroswki, David J.; Herr, Daniel L.; Dolly, Katelyn; Rabinowitz, Ronald P.; Scalea, Thomas M.; Menaker, Jay
Abstract : The purpose of this study was to evaluate survival to hospital discharge for patients on venovenous extracorporeal membrane oxygenation (VV ECMO) when stratified by age. We performed a retrospective study at single, academic, tertiary care center intensive care unit for VV ECMO. All patients, older than 17 years of age, on VV ECMO admitted to a specialized intensive care unit for the management of VV ECMO between August 2014 and May 2018 were included in the study. Trauma and bridge-to-lung transplant patients were excluded for this analysis. Demographics, pre-ECMO and ECMO data were collected. Primary outcome was survival to hospital discharge when stratified by age. Secondary outcomes included time on VV ECMO and hospital length of stay (HLOS). One hundred eighty-two patients were included. Median P / F ratio at time of cannulation was 69 [56–85], and respiratory ECMO survival prediction (RESP) score was 3 [1–5]. Median time on ECMO was 319 [180–567] hours. Overall survival to hospital discharge was 75.8%. Lowess and cubic spline curves demonstrated an inflection point associated with increased mortality at age >45 years. Kaplan-Meier analysis demonstrated significantly greater survival in patients <45 years of age ( p = 0.0001). Survival to hospital discharge for those <age 45 years was 84.6%. Comparatively, survival to hospital discharge for those ≥45 years was significantly lower (67.0%; p = 0.009), as was survival for those 55 years (57.1%; p = 0.001) and patients age ≥65 years (16.7%; p = 0.003). Patients 65 years of age and older treated with VV ECMO support for respiratory failure have low rates of survival to discharge. We have shown that age is an independent predictor of survival to discharge and beginning at age 45 years, in-hospital mortality increases incrementally. Moving forward we believe criteria and scoring systems for VV ECMO should include age as a variable.